Sources of success of ASTOR company on the Polish market - Kowalska, Katarzyna (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2021)
The article consists of an introduction, a conclusion and two chapters of theoretical and empirical character. The first section presents the most important assumptions of the new paradigm in business - the so-called four-leaf clover. It also points out on the importance of competencies and their development in the process of gaining competitive advantage on the changing market. The second part of the article is a case study. Using the example of the Polish company ASTOR, the practical application of the four-leaf clover formula was presented. It discusses how the organisation’s managers understand and conduct business. The paper uses a descriptive method with the use of literature analysis and desk research of existing data, as well as a combination of the diagnostic survey method and the method of analysis of individual case observation with the use of an in-depth interview questionnaire. The aim of this article is to identify the sources of ASTOR’s success on the Polish market. It allowed for a formulation of a hypothesis: The key success factor that ensures operational efficiency, brand differentiation and unique organisational culture is a professional approach to business based on humanistic values.